High-Resolution Optical Imaging and Sensing Using Quantum Emitters in Hexagonal Boron-Nitride - Bradac, Carlo (Frontiers in Physics, 2021)
Super-resolution microscopy has allowed optical imaging to reach resolutions well beyond the limit imposed by the diffraction of light. The advancement of super-resolution techniques is often an application-driven endeavor. However, progress in material science plays a central role too, as it allows for the synthesis and engineering of nanomaterials with the unique chemical and physical properties required to realize super-resolution imaging strategies. This aspect is the focus of this review. We show that quantum emitters in two-dimensional hexagonal boron nitride are proving to be excellent candidate systems for the realization of advanced high-resolution imaging techniques, and spin-based quantum sensing applications.